General practitioners’ experiences with children and adolescents with functional gastro-intestinal disorders: a qualitative study in Norway - Anne Brodwall; Mette Brekke (Scandinavian Journal of Primary Health Care, 2021)
Objective: Functional gastrointestinal disorders (FGIDs) are common in children and adolescents. During 2016 and 2019, we investigated the experiences among parents of children with FGIDs and interviewed their children and adolescents during 2020. The aim of the present study was to explore the experiences among general practitioners (GPs) who treat this patient group. Design: Individual interviews with open-ended questions were audio recorded and transcribed, and subsequently analysed using descriptive content analysis. Setting: Urban and rural areas in two municipalities in Southern Norway. Participants: Twelve GPs practicing in the region were interviewed. Results: GPs generally feel competent treating these patients without referring them to hospital or specialists. Having known the patients and their families over time is important. Providing psycho-educational resources to the patients and parents is essential for their understanding that the pain is not dangerous. The importance of attending school was emphasised. Conclusions: The GPs' biopsychosocial focus and long-term follow-up care are essential in treating children and adolescents with FGIDs and their parents. KEY POINTS Current awareness Abdominal pain is a common symptom in children and adolescents, for which an organic cause is seldom found. Main statements GPs feel competent to treat children and adolescents who have functional gastro-intestinal disorders (FGIDs) without referring them to hospital or specialists. • A main task for GPs is to inform children, adolescents, and their parents that FGIDs are not a serious organic disease and that everyday life should continue.